Role of Missionaries in Education: A Study of Nineteenth Century Nadia - Hasan, Jahid; Khan, Enayatullah (Summerhill IIAS Review, 2024)
The district of Nadia was a historically significant region of India in terms of education and culture. The Navadwip region of Nadia was renowned for its Sanskrit education since the medieval period. The Charter Act of 1813 came in favor of Christian missionaries, which allowed them to carry out their missionary activities and encouraged moral development in India. As a result, missionary activities expanded significantly in Bengal during the nineteenth century. Various Christian missionary societies like The Baptist Mission Society, The London Missionary Society, The Church Missionary Society, The Netherland Missionary Society and many others started to come to Bengal. The Church Missionary Society arrived on the land of Nadia for the first time in 1832. After that, the Roman Catholic Mission arrived here around 1840. A Catholic organization called Sisters of Charity also came to Nadia in 1860. Besides this, the Church of England Zenana Mission Society started its work in this region in 1885. Nadia soon became an important centre for Christian missionaries. Apart from religious preaching, they focused on education, health, social welfare and reforms in the local areas. The entire Christian Missionaries’ contributions to the development of education and health in Nadia are undeniable. Through this paper, it has been attempted to analyze and evaluate the contribution of Christian missionaries in the development of education during the nineteenth century Nadia.